Ethics in Nepalese Civil Services Sector: How does it matter? - Shakya, Umesh R (Administration and Management Review, 2010)
The objective of this paper is to highlight moral crises arising out of its fast devaluation that has affected almost every section of the society including bureaucracy. Nepalese civil services sector has increasingly become dysfunctional, fragmented, poorly organized, and incapable of performing at a level acceptable to the public. In recent years, Nepalese civil service has become too much politicized which has contributed to the promotion of unethical practices in civil service. As a result, moral & ethical values in civil services are in the state of deterioration, causing services delivery to suffer. Genuine concerns of law-biding citizens are consistently ignored, rules and regulations are constantly by-passed, ethics and morality have become a thing of past. Civil servants and higher government officers were unable to create an impression among the public that they are there to serve. A rapid deterioration in their ethics has made it difficult to generate in them the feeling of serving the public interest, demonstrating personal integrity, promoting ethical work environment, and striving for professional excellence. The author argues that to address this situation, what is needed is a civil service characterized by honesty, knowledge, skills, better performance and above all one that respects ethical value. It is necessary to restore the feelings that to be a member of bureaucracy is an honor and that it must continue to do all that is needed to help promote this image. He maintains that ethical issues in Nepalese civil services are and will remain important for improving service delivery. Key Words: Ethics in Nepalese Civil Services Sector; Law-biding citizens; Nepal Administration and Management Review Volume 21, No. 2, 2009 Page: 88-107